Subjective versus objective knowledge of online safety/dangers as predictors of children's perceived online safety and attitudes towards e-safety education in the United Kingdom. Issue 3 (2nd July 2020) - Macaulay, Peter J. R.; Boulton, Michael J.; Betts, Lucy R.; Boulton, Louise; Camerone, Eleonora; Down, James; Hughes, Joanna; Kirkbride, Chloe; Kirkham, Rachel
ABSTRACT: Children are spending increasing amounts of time online prompting practitioners and parents to raise concerns about their online safety. However, the impact of children's subjective versus objective knowledge on their perceived online safety and attitudes towards e-safety education remain unclear. Questionnaires were used to assess children's (N = 329, aged 8–11 years) perceived online safety, subjective and objective knowledge of online safety/dangers, and attitudes to e-safety education. While participants generally reported feeling safe online and perceived that they had a good awareness of online dangers and how to avoid them (subjective knowledge), they tended to be poor at articulating for themselves exactly what those dangers were and how they personally could elude them (objective knowledge). This was especially true of boys and younger children. Moreover, only subjective knowledge of online safety/dangers significantly predicted perceived online safety. Together, these findings suggest that some children may think that they know how to stay safe online but lack – or at least be unable to articulate – objective knowledge that could actually keep them safe. Consequently, there is a need to assess children's objective knowledge of online safety/dangers and to provide appropriate education for children who currently lack it.